Levels of Food Consumption Expenditure in Rajasthan: A Statistics Analysis - Dr Chhotu Ram (Innovative Research Thoughts, 2023)
In the economic development of the any nation, the three components- income, consumption and saving are most important indicators for the development process. According to Keynes, when income increases the consumption will also increase but not in the same proportion. So, according to Keynes if the gap between income and consumption (saving) is not covered into investment, it does create the problems of unemployment. The component of consumption is, therefore, most important for the development process. As a result of rapid urbanization, rising consumerism and changing lifestyles, the levels and patterns of the country’s food consumption expenditure has also begun to change. The consumption expenditure function is a good indicator of the economy status and the standard of living and also shows the relative importance of individual items in the consumption basket .Therefore, in this paper any attempt has been made to analyze and compare the consumption level of some of the most important food items in the urban and rural areas of India. An attempt has been made to estimate the marginal proposed to come consume (MPC) of these items of consumption through regression analysis.